2005
DOI: 10.1021/je050210x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Aqueous Sodium Glycinate Solution as an Absorbent for Carbon Dioxide Removal

Abstract: The physicochemical properties of aqueous sodium glycinate solution such as density, viscosity, surface tension, alkalinity, and pH were measured over a wide range of mass fraction (0.1 to 0.5) of sodium glycinate and at T ) (303.15 to 353.15) K. The measured data were correlated with standard equations, and parameters were reported along with average absolute deviations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 29 publications
1
49
2
Order By: Relevance
“…Holst et al (2006) compared the apparent absorption rate constants of CO 2 with different amino acid salt solutions and concluded that they were comparable with alkanolamines. Recently Lee et al studied the physical properties and the absorption kinetics of sodium glycinate as an absorbent of carbon dioxide (Lee et al, 2005(Lee et al, , 2007Song et al, 2006). However, the data available in literature are still too limited to permit a suitable design and optimization of processes using amino acid absorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Holst et al (2006) compared the apparent absorption rate constants of CO 2 with different amino acid salt solutions and concluded that they were comparable with alkanolamines. Recently Lee et al studied the physical properties and the absorption kinetics of sodium glycinate as an absorbent of carbon dioxide (Lee et al, 2005(Lee et al, , 2007Song et al, 2006). However, the data available in literature are still too limited to permit a suitable design and optimization of processes using amino acid absorbents.…”
Section: Introductionmentioning
confidence: 99%
“…This prompted us to study the aqueous SG solution as an absorbent for CO 2 . In our previous papers, we have reported the physical properties of SG solution and physical solubility and diffusivity of CO 2 in aqueous SG solution [21][22][23]. In continuation of this, we have measured the solubility of CO 2 in aqueous SG solutions of 10, 20, and 30 mass% at 303.15, 313.15, and 323.15 K over the pressure range (1-210 kPa) which would be utilized for the design, operation, and optimization of acid gas treatment equipment and also for measuring other chemical properties such as kinetic reaction, regeneration energy, and enthalpy of reaction [24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Both Tables and highlight the existence of trade-offs between different desirable features. No sorbent performs perfectly across all metrics, but many perform sufficiently well to result in low thermodynamic and economic costs of CO 2 avoided and successful implementation in practice. Finding acceptable trade-offs can be an effective way to identify promising sorbents.…”
Section: Comparing Sorbentsmentioning
confidence: 96%